2022
DOI: 10.1186/s40337-022-00698-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between social media exposure, food craving, cognitive impulsivity and cognitive restraint

Abstract: Background Young adults are increasingly exposed to social media and their image/video-based activities. They use these platforms to share images, videos and advice in different fields like food and nutrition with: recipe ideas, nutritional opinions or specific diets. Along with the rise of digital technologies, the prevalence of eating disorders in young adults continues to grow. The present study analyzes the psychological and eating processes through which exposure to social media may lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 100 publications
0
4
0
1
Order By: Relevance
“…Moreover, it is evident that exposure to digital marketing has an impact on young people’s attitudes and habits toward a range of unhealthy products [ 41 ]. Our finding may be explained by the fact that there is a relationship between social media exposure and food cravings in young adults [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is evident that exposure to digital marketing has an impact on young people’s attitudes and habits toward a range of unhealthy products [ 41 ]. Our finding may be explained by the fact that there is a relationship between social media exposure and food cravings in young adults [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting the notion that reward drive plays a role at the subclinical level (like found in the alcohol literature above) and that other processes such as the tendency to seek out appetitive foods and engage in binge-eating episodes play intermediary roles in the pathway to compulsive overeating, Loxton and Tipman [85] found that knowing that food is available and self-reported binge-eating mediated self-reported reward drive and food addiction symptom count. Trait impulsivity is also found to be associated with binge-eating, uncontrolled eating, and food cravings (e.g., [62,67,76]; See Table 2), although Loxton and Tipman [85] still found the indirect effect between reward drive and food addiction symptom count to hold when controlling for self-report rash impulsiveness.…”
Section: Foodmentioning
confidence: 99%
“…Binge eating didefinisikan sebagai keinginan mengonsumsi makanan dalam jumlah besar dan sulit untuk dikendalikan. Meningkatnya kecanduan penggunaan media sosial diketahui bersamaan dengan meningkatnya nilai body mass index (BMI) (Ayyıldız & Şahin, 2022;Filippone et al, 2022).…”
Section: Intensitas Penggunaan Media Sosial Dengan Kebiasaan Makanunclassified